Effect of MoSe2 nanoribbons with NW30 edge reconstructions on the electronic and catalytic properties by strain engineering. Issue 5 (23rd January 2023) - Gao, Nan; Yang, Xiaowei; Chen, Jinghuang; Chen, Xinru; Li, Jiadong; Fan, Junyu
Abstract : MoSe2 nanoribbons with NW30 edge reconstructions increase the dynamic stability and catalytic activity by DFT investigation. Abstract : Monolayer transition metal dichalcogenides (TMDs), typical two-dimensional semiconductors, have been extensively studied for their extraordinary physical properties and utilized for nanoelectronics and optoelectronics. However, the finite samples and discontinuity in the synthesis process of TMD materials definitely induce defect edges in nanoribbons and greatly influence the device performance. Here, we systematically studied the atomic structures, energetic and mechanical stability, and electronic and catalytic properties of MoSe2 nanoribbons on the basis of experiments. Clear benefits of ZZSe-Mo-NW30 edged nanoribbons were found to evidently increase the dynamic stability according to our first-principles calculations. Meanwhile, unsaturated Mo atoms at the edge sites induced local magnetic moments up to 0.54 μ B and changed the chemical environments of adjacent Se atoms, which acted as active sites for the hydrogen evolution reaction (HER) with a lower onset potential of −0.04 eV. The external tensile strain on these nanoribbons can have negligible effects on the electronic and catalytic properties. The onset potential of the ZZSe-Mo-NW30 edged nanoribbons only changed 0.03 eV under critical tensile strain. The atomic-scale research of edge reconstructions in TMD materials provides new opportunities to modulate the synthesis mechanism for experiments and defect-engineering applications in electrochemical catalysts.